Sosialisasi Kualitas Air tanah Kelurahan Pengkok, Kapenewon Patuk, Kabupaten Gunung Kidul, Yogyakarta - Prita Hanani; Dina tania; Eben Patriot Maury; Doris M Mausuati; Skolastika Intanari; Muhammad Rizky Wahyu (JNANADHARMA, 2024)
Until now, both deep and shallow groundwater is still the main source of clean water for residents in Pengkok Village, Patuk Subdistrict, Gunung Kidul Regency. Groundwater is the choice because it is easily obtained by pumping and the quality is good so that no complete treatment is needed for use. Groundwater quality tests were conducted to determine the feasibility of groundwater quality used by the Pengkok Village community to meet their daily water needs. Water quality parameters are divided into three parts, Physical parameters, are water quality parameters that can be analyzed or observed based on physical and visual characteristics. Chemical parameters are water quality parameters that are viewed from the composition of elements or chemical compounds contained in them, both organic compounds and inorganic compounds. Biological parameters, namely water quality parameters in terms of the content of microorganisms in it. From the analysis of the results of taking water samples from the 5 points, the physical test values were found to be compliant except for location 4 which had a turbidity value above the threshold and had a fishy odor. For chemical tests, only location 4 has iron (Fe) content above the quality standard, and location 5 has Manganese (Mn) value above the quality standard. As for biological tests, only location 3 and location 4 are safe from Escherichia coli bacteria, and location 1 is contaminated with the most Escherichia coli bacteria.